Immunological and clinical characteristics of latent autoimmune diabetes in the elderly - Yohena, Silvina (2019)
Background: Latent autoimmune diabetes in adults (LADA) is determined by both a noninsulin-dependent clinical presentation and an autoimmune pathogenic process. Glutamic acid decarboxylase antibody (GADA) constitutes the most important marker, although IA-2A and ZnT8A also define LADA presentation. Type 2 diabetes mellitus (T2DM) is the most prevalent type particularly over 65 years old. Studies about autoimmunity in this age group are scarce. Objective: The aim of this work was to determine whether three autoantibodies for diabetes autoimmunity were present in elderly T2DM patients, and to assess the distinctive clinical features of autoantibody-positive patients. Research Design and Methods: We recruited 153 patients with diabetes with onset of diabetes after 65 years of age and a BMI under 30 kg/m2. Results: The prevalence of at least one of the autoantibodies was 15.68% (24/153). The most prevalent autoantibody was GADA with 8.49% (13/153), followed by ZnT8A with 6.50% (10/153) and IA2A with 1.96% (3/153). The autoimmunity-positive group presented higher HbA1c (7.01 ± 1.98 vs 6.35 ± 1.01; P = 0.007) and more prevalent insulin therapy (25% vs 10.85%; P = 0.047). GADA-positive patients with diabetes presented higher FPG (7.79 ± 3.79 mmol/L vs 6.43 ± 1.6 mmol/L; P = 0.014) and insulin therapy more frequently (46% vs 10.71%; p = 0.015). GADA titre levels in the individuals with BMI under 27 kg/m2 were higher (35.00 ± 4.20) than those in the group with BMI over 27 kg/m2 (8.83 ± 3.041; P = 0.0005). Conclusion:: Autoantibodies GADA and Znt8A may be useful markers in identifying a subgroup of older patients with a clinical presentation of diabetes which could be characterized as latent autoimmune diabetes in the elderly.